High Prevalence of Low Muscle Strength and Poor Physical Performance in Pre-Elderly and Elderly Communities in Rural Cirebon, Indonesia: A Public Health Measurement Initiative - Safira, Nanda; Nasution, Lailan Safina (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
Introduction: Sarcopenia, characterized by progressive muscle decline, threatens functional independence and global health sustainability. Early identification of low muscle strength is critical in community settings that lack advanced diagnostic tools. This cross-sectional study aimed to measure the prevalence of low muscle strength and identify key physical factors in a combined pre-elderly (45-59 years) and elderly (≥ 60 years) cohort, aligning with the concept of community-based physical fitness measurement. Methods: We conducted a cross-sectional study among 62 participants (67.7% female; 61.3% elderly) in Cirebon, Indonesia. Probable sarcopenia was screened using the Asian Working Group for Sarcopenia (AWGS 2019) criteria: Low Muscle Strength (handgrip < 28 kg for men, < 18 kg for women) and Low Physical Performance (≥ 12.0 sec chair stand). Analysis included non-parametric tests and a multivariate logistic regression adjusting for age and calf circumference. Results: Low muscle strength prevalence was high at 66.1% (n = 41). Strength was significantly higher in males (20.30 kg) than females (15.66 kg, p-value = 0.004). Physical performance was poor, with 80.6% of the population meeting the criteria for slowness (median = 13.98 sec). Multivariate analysis identified calf circumference as a significant independent protective factor for both low strength (AOR: 0.77; 95% CI: 0.62–0.92; p-value = 0.008) and poor performance (AOR: 0.77; 95% CI: 0.57–0.96; p-value = 0.043). Advanced age was a significant predictor specifically for low muscle strength (AOR: 4.41; 95% CI: 1.23–17.6; p-value = 0.026). No significant associations were found with body mass index (BMI), blood sugar, cholesterol, smoking, or job status (p-value > 0.05). Conclusion: The high prevalence of low muscle strength in this pre-elderly and elderly cohort, independently predicted by smaller calf circumference, signals a critical public health threat. This functional decline is primarily driven by physical and age-related factors, not socioeconomic status. Our findings demand urgent, community-based strength training programs to empower healthy aging and preserve functional independence.